2020
DOI: 10.3892/mmr.2020.11510
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin‑1 as a new potential SARS‑CoV‑2 infection mediator implicated in the neurologic features and central nervous system involvement of COVID‑19

Abstract: infection by the severe acute respiratory syndrome (SarS) coronavirus-2 (SarS-coV-2) is the cause of the new viral infectious disease (coronavirus disease 2019; coVid-19). emerging evidence indicates that coVid-19 may be associated with a wide spectrum of neurological symptoms and complications with central nervous system (cnS) involvement. it is now well-established that entry of SarS-coV-2 into host cells is facilitated by its spike proteins mainly through binding to the angiotensin-converting enzyme 2 (ace-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(171 citation statements)
references
References 35 publications
3
163
0
5
Order By: Relevance
“…Recent work showed that the NTD of SARS-CoV-2 may bind cellular receptors other than ACE2 and mediate the entry of the virus into cells that do not express ACE2 [35]. Furthermore, the cell-surface protein neuropilin-1 has been reported to facilitate SARS-CoV-2 cell entry, especially into brain cells [36][37][38], although the mechanism is not fully understood.…”
Section: The Spike Glycoproteinmentioning
confidence: 99%
“…Recent work showed that the NTD of SARS-CoV-2 may bind cellular receptors other than ACE2 and mediate the entry of the virus into cells that do not express ACE2 [35]. Furthermore, the cell-surface protein neuropilin-1 has been reported to facilitate SARS-CoV-2 cell entry, especially into brain cells [36][37][38], although the mechanism is not fully understood.…”
Section: The Spike Glycoproteinmentioning
confidence: 99%
“…Therefore, we cannot exclude the possibility that the increase in fusion observed when TMPRSS2 is present in these cells is due to an effect on hACE2. In addition to the effect of proteases on cell-cell fusion, we also assessed the effect of Neuropilin-1, which has been suggested to be a co-receptor for SARS-CoV-2 viral entry and may be key for SARS-CoV-2 infiltration of the neuronal network [ 53 55 ]. We show that the presence of Neuropilin-1 with hACE2 in target cells does not impact S mediated cell-cell fusion ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropilin-1 has been suggested as a co-receptor for SARS-CoV-2 S and may be important for the viral infection infiltrating the neuronal network [53][54][55]. To assess the contribution of neuropilin in cell-cell fusion, effector cells were transfected with S and either EV, furin, neuropilin, or furin and neuropilin (F+N).…”
Section: Spike Mediated Cell-cell Fusionmentioning
confidence: 99%
“…Two main hypotheses have been proposed for brain entry and propagation throughout the central nervous system: 1) via the bloodstream; 2) through the olfactory epithelium of the nasal cavity and olfactory bulb via retrograde transport along axons of olfactory sensory neurons [ 22 , 121 , 122 ]. On the other hand, recent evidences support the theory of direct neurotropism of SARS-CoV-2, as the RNA of this virus was detected in the cerebrospinal fluid of a patient with COVID-19 [ 22 ].…”
Section: Msc: Multi-organ Protection Against Acute Injury?mentioning
confidence: 99%
“…Moreover, sincethe ACE2 receptor is expressed in brain endothelium, SARS‑CoV‑2 can enter into the CNS by interacting with ACE‑2 of the capillary endothelium leading to blood‑brain‑barrier (BBB) disruption. BBB can also be damaged by neuroinflammation as a result of the cytokine storm [ 122 , 123 ].…”
Section: Msc: Multi-organ Protection Against Acute Injury?mentioning
confidence: 99%